M-Type Potassium Channels Modulate the Intrinsic Excitability of Infralimbic Neurons and Regulate Fear Expression and Extinction - Santini, Edwin (Society for Neuroscience, 2010)
Growing evidence indicates that the activity of infralimbic prefrontal cortex (IL) is critical for inhibiting inappropriate fear responses following extinction learning. Recently, we showed that fear conditioning and extinction alter the intrinsic excitability and bursting of IL pyramidal neurons in brain slices. IL neurons from Sprague Dawley rats expressing high fear had lower intrinsic excitability and bursting than those from rats expressing low fear, suggesting that regulating the intrinsic excitability and bursting of IL neurons would modulate fear expression. To test this, we combined patch-clamp electrophysiology, auditory fear conditioning, and IL infusions of M-type K(+) channel modulators. Patch-clamp recordings from IL neurons showed that the M-type K(+) channel blocker, XE-991, increased the number of spikes evoked by a depolarizing pulse and reduced the first interspike interval indicating enhanced bursting. To test whether pharmacological enhancement of IL excitability and bursting reduces fear expression and facilitates extinction, fear-conditioned rats were infused with XE-991 into IL before extinction training. XE-infused rats showed reduced freezing and facilitated extinction compared to vehicle-infused rats. The following day, recall of extinction memory was enhanced. Reducing IL excitability and bursting with the M-type K(+) channel agonist, flupirtine, had the opposite effect. Flupirtine reduced IL spike count and bursting in brain slices. Fear-conditioned rats infused with flupirtine into IL before extinction showed significantly higher levels of freezing, indicating that stimulation of M-channels enhanced fear expression. Our findings suggest that the intrinsic excitability and bursting of IL neurons regulate fear expression even before extinction.